The effect of exercise training on pulmonary function and aerobic capacity in adults with burn - Grisbrook, Tiffany; Wallman, K.; Elliott, Catherine; Wood, Fiona; Edgar, Dale; Reid, S. (Pergamon, 2012)
Purpose: Pulmonary function (PF) is compromised in some individuals following burn, which may result in impaired aerobic capacity. Exercise training improves PF and exercise capacity in children recovering from burns, yet it is unknown if adults will demonstrate the same response.Procedures: 9 burn injured participants (%TBSA 42 18.38, 6.56 years 3.68 post injury) and 9 matched controls participated in a 12-week goal directed interval training and resistance exercise programme. PF was measured using spirometry, and a graded exercise test quantified peak oxygen consumption ð ?VO2peak Þ, both prior to and following the exercise training. The Canadian Occupational Performance Measure assessed the participant’s goal attainment.Results: Burn injured participants had significantly lower PF (FEV1/FVC ratio) than the healthy controls both prior to and following the exercise intervention (F(1,16) = 8.93, p = 0.009). Exercise training did not improve PF in either group, however both groups had a significant improvement in their ?VO2peak , maximal minute ventilation, and work achieved on a graded exercise test (F(1,16) = 19.325, p < 0.001), (F(1,16) = 51.417, p < 0.001) and (F(1,16) = 36.938, p < 0.001), respectively, following the exercise training. All participants achieved their occupational performance goals.Conclusion: Although the exercise training did not alter PF, both aerobic capacity and occupational performance were improved.